The COVID-19 outbreak: April 2021 update - Temte, Jonathan (Henry Stewart Talks, 2021)
Changes in COVID-19 epidemiology since October 2020, The effect of the SARS-CoV-2 strains on epidemiology, The development and rollout of vaccines, How higher transmission leads to more SARS-CoV-2 strains